Assessing Gender Differences in Outcomes Post-Percutaneous Coronary Intervention - Afzal, Zeeshan; Khan, Farhat Ullah; Akhtar, Syed Ahsan; Khan, Naeem; Hafeez, Muhammad (Indus Journal of Bioscience Research, 2025)
Introduction: Gender disparities in cardiovascular outcomes have been observed globally, yet limited local data exists assessing these differences post-percutaneous coronary intervention (PCI) in Pakistan. Objective: To assess gender-based differences in clinical outcomes, symptom recurrence, complication rates, and quality of life following PCI in a tertiary care hospital in Pakistan. Materials and Method: A prospective observational study was conducted at Department of Cardiology, Hayatabad Medical Complex, Peshawar from July, 2021 to December, 2021. A total of 300 patients (180 males, 120 females) who underwent PCI were enrolled. Data on demographics, comorbidities, procedural outcomes, and post-discharge follow-up were collected and analyzed using SPSS v26. Results: Females were older and had higher rates of hypertension and diabetes. They experienced more bleeding events (12% vs. 5%), vascular complications, and lower post-PCI quality of life. Persistent chest pain and adverse cardiac events were also more frequent in females. Conclusion: Significant gender-based disparities exist post-PCI, highlighting the need for gender-specific treatment and follow-up strategies.